SEASONAL VARIATION OF TRACE ELEMENT IN SUSPENDED PARTICLE AT SAKAERAT BIOSPHERE RESERVE FOREST, NAKHON RATCHASIMA PROVINCE - Sangkachai, Bantita; Tammadid, Wittanan; Chanonmuang, Phuvasa; Silprasit, Kun; Prueksakorn, Kritana; Hanpattanakit, Phongthep (Srinakharinwirot University Journal of Sciences and Technology, 2023)
This research focused on atmospheric trace elements contamination in particulate matter (PM) at rural area, which a major cause of health ecosystem and environmental impacts. The research aimed to study the relationship between dust particles and environmental factors, examine the annual variation in particulate matter as PM2.5 and PM10 and investigate for heavy metals concentrations at dry dipterocarp forest, Sakaerat Environmental Research Station (SERS), Nakhon Ratchasima province, Thailand. The trace element for 5 heavy metals consist of selenium (Se), arsenic (As), iron (Fe), cadmium (Cd), and lead (Pb). The air sampling was collected by 2 stage filter pack at 5 meter above the ground for 5 days per month, from January to December 2019. The results demonstrated that the yearly average concentrations of PM2.5 and PM10 were 23.00±17.11 and 8.17±5.52 µg/m3. The contamination of PM2.5 between wet and dry seasons were significant different (p-value < 0.05) and the maximum value of PM2.5 was 59.72 µg/m3 in March. While, the heavy metals in fine particulate matters were not significant different with seasonal variation (p-value < 0.05). Thus, the average concentration of heavy metals was Se > As > Fe > Cd > Pb as 0.79±0.39, 0.48±0.21, 0.31±0.18, 0.23±0.13, and 0.14±0.22 µg/m3 – which account for 41%, 24%, 16%, 12%, and 7%, respectively. In this study, Se, As and Pb were maximum contaminated in fine particulate matter in May as 1.62, 0.96 and 0.79 µg/m3, respectively.